The identification of Cryptosporidium species in stool samples using alternative diagnostic methods - Al-Alwani, Z. K. A.; Alouci, M. M. Al; Alkhazraji, K. A. J. (Regulatory Mechanisms in Biosystems, 2025)
Cryptosporidiosis, caused by Cryptosporidium species, leads to gastrointestinal issues, especially in immunocompromised individuals. Alternative diagnostic methods like PCR and ELISA offer more sensitive and accurate identification of Cryptosp o ridium in stool samples compared to traditional microscopy. We e valuate d the effectiveness of alternative diagnostic methods, namely PCR , in identifying Cryptosporidium species in stool samples compared to traditional microscopy. This cross-sectional study was conducted from March 15, 2022 to September 15, 2023 at Ramadi Pediatric General Hospital, Ramadi General Teaching Hospital, and selected private medical laboratories. It included 320 patients (aged 18 – 77) with gastroenteritis sym p toms. Stool samples were collected and analyzed microscopically using various staining methods, including modified Ziehl-Neelsen and fluorescence techniques. DNA extraction and nested PCR were performed to detect Cryptosporidium spp. Micr o scopic stool examination revealed a 10% infection rate with Cryptosporidium (32/320 samples), with higher infection rates in older adults (23.1% in 74–83 years) and retirees (17.9%). Males (10.2%) and rural residents (10.9%) had higher infection rates. Seasonal variation showed the highest rates in April (22.7%). PCR showed greater sensitivity than microscopy, detecting three additional positive samples. Diagnostic accuracy of microscopy, compared to PCR, was 90.6%, with high sensitivity (100%) and specificity (88%). Concordance between microscopy and PCR was 90.6%, with three discordant cases. Microscopy and PCR showed high concordance in diagnosing Cryptosporidium infections, with PCR offering higher sensitivity. The seasonal vari a tion and higher infection rates in older adults and rural areas suggest environmental factors and compromised immunity contr i bute to increased susceptibility.